Handbook of Clean Energy Systems 2015
DOI: 10.1002/9781118991978.hces135
|View full text |Cite
|
Sign up to set email alerts
|

Algae Biofuels

Abstract: Biofuels represent today a global commodity, with 110 billion liters produced in 2012, covering approximately 3% of world's transport fuel demand (on an energy equivalent base): IEA estimates that the world biofuels production will reach 2.36 mb/day (135 billion liters/year) in 2018, equal to 4% road transport fuel demand, an increase of 0.48 mb/day compared to 2012. In parallel to increased production, thanks to advanced biofuel technology development and commercialization, further opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…We found that the LMBRs deserved proper exploitation as fertilizer substitute as they are rich in plant nutrients. Considering the state of the art of algal production and post-harvest technology, the current production of biofuel from microalgae is technically feasible, but its economic feasibility is still a major challenge (Chiaramonti et al, 2015 ). The results of the present experiment applying the biorefinery concept to valorize the LMBR as a plant nutrient source is one of the ways to achieve economic sustainability of algal biofuel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the LMBRs deserved proper exploitation as fertilizer substitute as they are rich in plant nutrients. Considering the state of the art of algal production and post-harvest technology, the current production of biofuel from microalgae is technically feasible, but its economic feasibility is still a major challenge (Chiaramonti et al, 2015 ). The results of the present experiment applying the biorefinery concept to valorize the LMBR as a plant nutrient source is one of the ways to achieve economic sustainability of algal biofuel.…”
Section: Discussionmentioning
confidence: 99%
“…The biofuel sector is specifically interested in carbohydrates (mainly C6) and lipids (mainly C16–C22), the amount of which could vary as a function of the algae species, strains, and the cultivation methods adopted (Chiaramonti et al, 2015 ). The current worldwide algae biomass production has been projected to be at more than 20,000 dry tons per year (Verdelho, 2013 ; Zittelli et al, 2013a , b ; Chiaramonti et al, 2015 ). However, the algae market is expected to grow as the constraints of algal production are overcome and the cost of production is reduced.…”
Section: Introductionmentioning
confidence: 99%